Composição química e potencial farmacológico do óleo essencial de Lippia hermannioides - Oliveira, Áddla Thaine Santos (2023)
The genus Lippia, which belongs to the Verbenaceae family, has a high potential in folk medicine, with species used in the treatment of various illnesses, especially those linked to the respiratory and gastrointestinal systems. Lippia hermannioides Cham. is an endemic species from Brazil and it has already had its antioxidant and antimicrobial activity revealed. The objective of this work was to determine the chemical composition of the essential oil from the leaves of Lippia hermannioides (OELH), through the use of chromatographic and spectrometric methods, and the antinociceptive and anti-inflammatory potential through the realization of chemical models (acetic acid and formalin) and thermal (hot plate) of nociception. The results revealed germacrene D (18.39%), bicyclogermacrene (11.72%), 1.8-cineol (11.24%), sabinene (10.38%), E-caryophyllene (8.33%), β-pinene (7.37%) and α-pinene (6.18%) as the major compounds present in the oil. The intraperitoneal administration of OELH at doses 300 and 2000 mg/kg did not show signs of toxicity in mice. At doses 75 and 300 mg/kg, the OELH did not affect the motor coordination of the animals in the test rota-rod, it decreased the number of abdominal contortions induced by acetic acid, reduced the paw licking time in both phases of the test formalin, as well as increased latency time in the hot plate test. These results indicate that the studied essential oil has antinociceptive and anti-inflammatory activity and suggest that its action can be mediated by peripheral and central mechanisms, thus providing support for future research with the purpose of using this phytogenetic resource in health.